Evaluating the effect of chitosan layer on bioaccessibility and cellular uptake of curcumin nanoemulsions - Silva, Hélder D. (2019)
Curcumin nanoemulsions stabilized by whey protein isolate were successfully developed using high-pressure homogenization. The effect of a chitosan layer deposition using the layer-by-layer technique on nanoemulsions' stability was evaluated during storage conditions, as well as during gastrointestinal tract passage. Lipids hydrolysis and curcumin bioaccessibility was assessed using a dynamic gastrointestinal model (simulating the stomach, duodenum, jejunum and ileum) and the cytotoxicity, cellular antioxidant activity and permeability analyses were carried out using Caco-2cells. Results showed that both nanosystems were stable during one month of storage and at stomach pH conditions, whereas creaming and phase separation occurred at intestine pH conditions. The addition of a chitosan layer increased curcumin bioaccessibility, whereas cellular antioxidant activity studies revealed that nanoemulsions and multilayer nanoemulsions exhibited 9 and 10 times higher antioxidant capacity at the cellular level, respectively, when compared to free curcumin. Permeability assays showed that the use of a chitosan layer significantly increased the apparent permeability coefficient of curcumin through Caco-2cells by 1.55-folds.